Endovascular thrombectomy in acute ischemic stroke patients with prestroke disability (mRS ≥2): A systematic review and meta-analysis - Yang, Jin-Cai; Bao, Qiang-Ji; Guo, Yu; Chen, Shu-Jun; Zhang, Jin-Tao; Zhang, Qiang; Zhou, Ping; Yang, Ming-Fei (Frontiers in Neurology, 2022)
Objective The effect of endovascular thrombectomy (EVT) in acute ischemic stroke patients with prestroke disability (modified Rankin Scale score, mRS) ≥2) has not been well-studied. This study aimed to assess the safety and benefit of EVT in patients with prestroke disability. Methods According to PRISMA guidelines, literature searching was performed using PubMed, Embase, and Cochrane databases, for a series of acute ischemic stroke patients with prestroke mRS ≥2 treated by EVT. Random-effects meta-analysis was used to pool the rate of return to prestroke mRS and mortality at 3-month follow-up. Results In total, 13 observational studies, with 2,625 patients, were analyzed. The rates of return to prestroke mRS in patients with prestroke mRS of 2–4 were 20% (120/588), 27% (218/827), and 31% (34/108), respectively. Patients with prestroke disability treated by EVT had a higher likelihood of return to prestroke mRS (relative risk, RR, 1.86; 95% CI 1.28–2.70) and a lower likelihood of mortality (RR 0.75; 95%CI 0.58–0.97) compared with patients with standard medical treatment. Successful recanalization (Thrombolysis in Cerebral Infarction grade 2b-3) after EVT gave a higher likelihood of return to prestroke mRS (RR 2.04; 95% CI 1.17–3.55) and lower mortality (RR 0.72; 95% CI 0.62–0.84) compared with unsuccessful reperfusion. Conclusions Acute ischemic stroke patients with prestroke disability may benefit from EVT. Withholding EVT on the sole ground of prestroke disabilities may not be justified. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/.